2019
DOI: 10.1007/s13205-019-1591-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of Dendrocalamus hamiltonii natural metapopulation: a commercially important bamboo species of northeast Himalayas

Abstract: Dendrocalamus hamiltonii is a commercially important bamboo species of India, experiencing population depletion due to heavy extraction from natural forests. Nuclear simple sequence repeats (nSSRs) were used to study the genetic diversity and population genetic structure of 19 natural stands of D. hamiltonii distributed across the northeast Himalayas. A total of 68 nSSR primer pairs of D. latiflorus and Bambusa arundinacea have been tested in D. hamiltonii for their transferability, out of which 17 primers sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…On the other hand, F SC = 0.10486, F ST = 0.38949 and F CT = 0.31797 in seven groups and F ST = 0.36354 without grouping were recorded from O. abyssinica populations of Ethiopia. F SC = 0.132, F ST = 0.187, and F CT = 0.062 in four groups and F ST = 0.165 without grouping were reported from D. hamiltonii (Meena et al., 2019). Higher population divergence or differentiation was observed in D. hamiltonii ( F ST = 0.165), and very great or significant genetic differentiation with F ST = 0.36354 was recorded in O. abyssinica populations.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, F SC = 0.10486, F ST = 0.38949 and F CT = 0.31797 in seven groups and F ST = 0.36354 without grouping were recorded from O. abyssinica populations of Ethiopia. F SC = 0.132, F ST = 0.187, and F CT = 0.062 in four groups and F ST = 0.165 without grouping were reported from D. hamiltonii (Meena et al., 2019). Higher population divergence or differentiation was observed in D. hamiltonii ( F ST = 0.165), and very great or significant genetic differentiation with F ST = 0.36354 was recorded in O. abyssinica populations.…”
Section: Discussionmentioning
confidence: 94%
“…ISSR markers analysis for the genetic relationship study of five native and economical important bamboos (Amom et al., 2020), for the genetic diversity and structure of Dendrocalamus hamiltonii (Meena et al., 2019) and for the population genetic study of Melocanna baccifera (Roxb.) Kurz (Nilkanta et al, 2017), revealed that most of the populations were clustered in accordance with their geographical distribution and location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of multiple alleles was encountered in our study performed for population genetic analysis in an Indian bamboo species, Dendrocalamus hamiltonii (Meena et al, 2019). This species belongs to the lineage palaeotropical woody bamboos whose genome is allohexaploid (2n = 6x = 72) containing genomes of different ancestral lineages (Thakur et al, 2015;Guo et al, 2019).…”
Section: Research Notementioning
confidence: 99%
“…While in group 2, a population of Assam was separated from other Assamese populations and unexpectedly clustered with the population of Meghalaya. The group wise clustering behavior of each population has been explained in our published article (Meena et al, 2019). Structure analysis was carried out to identify the ancestral gene pools and determination of inferred ancestry of individual populations in each defined cluster.…”
Section: Research Notementioning
confidence: 99%